2023
DOI: 10.3389/fphys.2023.1124696
|View full text |Cite
|
Sign up to set email alerts
|

From lymphatic endothelial cell migration to formation of tubular lymphatic vascular network

Abstract: During development, lymphatic endothelial cell (LEC) progenitors differentiate from venous endothelial cells only in limited regions of the body. Thus, LEC migration and subsequent tube formation are essential processes for the development of tubular lymphatic vascular network throughout the body. In this review, we discuss chemotactic factors, LEC-extracellular matrix interactions and planar cell polarity regulating LEC migration and formation of tubular lymphatic vessels. Insights into molecular mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Besides accounting for lymphatic capillary network rarefaction by increasing the number of myofibroblasts, Ly-EndMT may also contribute to preventing lymphatic microcirculation recovery by impairing lymphangiogenesis, a multistep process taking place in different conditions, including wound healing, inflammation, and cancer, during which new microlymphatics are shaped through the sprouting of ECs from pre-existing lymphatic structures [40,41]. In this context, our group has recently demonstrated that the pathologic SSc microenvironment is able to deeply hamper in vitro different steps of the lymphangiogenesis process, such as HdLy-MVEC proliferation, invasion, and wound healing capacity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides accounting for lymphatic capillary network rarefaction by increasing the number of myofibroblasts, Ly-EndMT may also contribute to preventing lymphatic microcirculation recovery by impairing lymphangiogenesis, a multistep process taking place in different conditions, including wound healing, inflammation, and cancer, during which new microlymphatics are shaped through the sprouting of ECs from pre-existing lymphatic structures [40,41]. In this context, our group has recently demonstrated that the pathologic SSc microenvironment is able to deeply hamper in vitro different steps of the lymphangiogenesis process, such as HdLy-MVEC proliferation, invasion, and wound healing capacity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Both ligands, Vegfc and Cxcl12 , are highly expressed by embryonic mesenchymal cells adjacent to the developing lymphatic vasculature (10, 12, 16, 19). Despite the knowledge gained in the mechanism supporting LEC migration in the past years (20), little is known how the final pattern of lymphatic vessels in different tissues of the embryo is achieved. Several cell types have been described to influence lymphatic vessel development in zebra fish and mice, such as platelets, arterial endothelial cells, neurons, myeloid cells and mural cells (12, 16, 21, 22).…”
Section: Introductionmentioning
confidence: 99%